2020
DOI: 10.1109/access.2020.2981190
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of Tail Shapes for Hummingbird-Like Flapping Wing Micro Air Vehicles

Abstract: The stability of flying of a hummingbird-like flapping-wing micro air vehicle (MAV) has been challenging. In this paper, experimental studies are reported on the tail shapes of hummingbird-like flappingwing MAVs, since tails play an important role in-flight stability. Dynamics parameters of hummingbird tails are firstly studied and evaluated. Then man-made tails inspired by the natural hummingbirds are designed, manufactured and optimized for experimental tests. The results show that lift generated by the tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…It should be noted that there is a possibility that the appropriate stiffness of the flexibilities could depend on both wing and body shapes. Previous studies have reported the importance of the wing shape and structure (Keennon et al, 2012;Nan et al, 2017) as well as the tail shape (Nan et al, 2020) to improve mechanical efficiency and aerodynamic lift force production. Therefore, it will be our future work to experimentally examine the effects of various wing shapes and flexibilities to generalize our results and improve FFM performance.…”
Section: Effect Of the Flexibility In The Flapping Mechanism On The Robustness Against The Disturbancementioning
confidence: 99%
“…It should be noted that there is a possibility that the appropriate stiffness of the flexibilities could depend on both wing and body shapes. Previous studies have reported the importance of the wing shape and structure (Keennon et al, 2012;Nan et al, 2017) as well as the tail shape (Nan et al, 2020) to improve mechanical efficiency and aerodynamic lift force production. Therefore, it will be our future work to experimentally examine the effects of various wing shapes and flexibilities to generalize our results and improve FFM performance.…”
Section: Effect Of the Flexibility In The Flapping Mechanism On The Robustness Against The Disturbancementioning
confidence: 99%
“…Considering the limited onboard power supply, the prototype demands high propulsion efficiency to generate sufficient thrust while consuming less power. To address that, the trapezoidal airfoil in [32] was adopted to improve the aerodynamic performance with a wing length of 78 mm and a mean chord length of ̅ 21 mm. The wings can be driven to flap at a natural frequency with the proper gains of the motor controllers, so that the aerodynamic lift can be tested.…”
Section: Wing Design and Manufacturingmentioning
confidence: 99%
“…As shown in Figure 4, the mean lift of the wing was measured by the F/T sensor (Nano-17, ATI Industrial Automation, North Carolina, USA), indicating that the flapping wing generated a maximum thrust of 11 gf while flapping at Considering the limited onboard power supply, the prototype demands high propulsion efficiency to generate sufficient thrust while consuming less power. To address that, the trapezoidal airfoil in [32] was adopted to improve the aerodynamic performance with a wing length of R w = 78 mm and a mean chord length of c = 21 mm. The wings can be driven to flap at a natural frequency with the proper gains of the motor controllers, so that the aerodynamic lift can be tested.…”
Section: Wing Design and Manufacturingmentioning
confidence: 99%
“…Secondly, data from natural birds were considered. Yanghai and et al [34] obtained the values of different tail aspect ratios (AR h ) in certain species of birds. Table 3 shows the tail aspect ratios.…”
Section: First Processing Phasementioning
confidence: 99%